Pengaruh Kualitas Produk Dan Ekuitas Merek (Brand Equity) Terhadap Minat Pembelian Ulang Produk INDOMIE (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Angkatan Tahun 2017 Universitas Islam Malang) - Iin Widyantasari; Nurhajati Nurhajati; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract  This study aims to determine the effect of product quality, brand equity on the intention to repurchase Indomie products. The dependent variable (Y) in this study is the intention to repurchase. The independent variable (X) in this study is Product Quality, Brand Equity. This research is an explanatory research. The data used by the researcher is primary data with the collection method using a questionnaire distributed to students of the 2017 Faculty of Economics and Business, Islamic University of Malang. The sampling technique used is Non-Probability Sampling with the type of Purposive Sampling. The number of samples used consisted of 90 respondents. Furthermore, the data is processed using SPSS to test statistics in the form of instrument tests, normality, classical assumptions, multiple linear regression and hypothesis testing. The results showed that product quality and brand equity had a significant effect on repurchase intention. Keywords: Product Quality, Brand Equity, Repurchase Interest